STUDI KELAYAKAN TERHADAP PROYEK LEMBAH SUNGAI MUSI BANYUASIN BAGIAN 1: STUDI UMUM SEDIMENTASI - Sohei Matsuno; Oktarina . (PERTETA, 2007)
ABSTRACT This is an extract of a feasibility-study report on the two projects, 'Consolidation of Infrastructure of Biofuel Industry,in Musi- Banyuasin regency and ditto in Banyuasin regency. PART 1 is of general studies on sediment in the Musi-Banyuasin River system where the project sites are located. The primary objective of this report is to forward solution to the sediment-origin problems, which is a compulsory subject for any projects in the Musf-Banyuasin River system. To attain this objective, it clears the following secondary objectives, viz. (a) identifying every problem hindering human lives and activities, (b) drawing a hypothesis about causality, (e) determining basic data by field surveys, lab tests and data analyses and (d) authenticating the hypothesis to be a theory. To achieve these objectives, the studies have gone forward with four represenfative objects, viz. (i) the Muba River system as a wholee, (ii) the lower reaches of the main stream, (iii) the biggest tributary ,and (iv) the biggest dis-tributary. It concludes that sediment is the sole cause of major problems, forwards measures to solve the problems, and suggests do's and don’ts. PART 2, 'Particular Studies on a Certain Project,' explains how the results of PART 1 are applied to the project. PART 1 leaves the verification of the suggested technical systems to full-scale/ in-situ model tests that are elaborated in PART 2 and to baexecuted in the first step of each project. Keywords: sedimant-effects, In-swamp irrigation / transportation Diterima: 8 Juli 2007; Disetujui: 22 Agustus 2007